Stage Conjuring with Film: Influences and Legacies. Issue 2 (3rd April 2018) - Waltz, Gwendolyn
ABSTRACT: Soon after the first public presentations of motion pictures at the end of the nineteenth century, film projection became a resource for stage magic. It could be used for practical purposes in creating illusions or, cleverly, to bridge transitions in the structure of a conjuring act. However, magicians also inventively employed film as a means to shape and explore new relationships arising between recorded-action and live-action when they were juxtaposed or integrated. Multimedia magicians built their work upon popular aesthetic themes, including nineteenth-century 'art to life' transformations, and used motion-picture technology to demonstrate new aspects of the modern magician's persona, such as 'scientific wizard' and 'ironic artist'. These new illusions would be adapted and updated by generations of magicians. Beyond the conjurors's stage, multimedia effects were among the performance concepts exchanged back and forth by artists who performed early twentieth-century variety acts, and several illusions continue to influence and be featured in live productions across the performing arts: theatre, dance, corporate shows, television and amateur presentations. These effects provide frameworks for modernist concepts (including 'meta' references, and temporal and spatial metamorphoses), which have contributed to their survival for over a century, supporting their modifications to video and digital technologies.